A comparison of load balancing techniques for scalable Web servers. - Bryhni, H.
Scalable Web servers can be built using a network of workstations where server capacity can be extended by adding new workstations as the workload increases. The topic of our article is a comparison of different method to do load-balancing of HTTP traffic for scalable Web servers. We present a classification framework the different load-balancing methods and compare their performance. In addition, we evaluate in detail one class of methods using a prototype implementation with instruction-level analysis of processing overhead. The comparison is based on a trace driven simulation of traces from a large ISP (Internet Service Provider) in Norway. The simulation model is used to analyze different load-balancing schemes based on redirection of request in the network and redirection in the mapping between a canonical name (CNAME) and IP address. The latter is vulnerable to spatial and temporal locality, although for the set of traces used, the impact of locality is limited. The best performance is obtained with redirection in the network
Keywords: HTTP traffic; IP address; ISP; Internet Service Provider; Norway; Canonical name; Instruction-level analysis; Load balancing techniques; Load-balancing.; Mapping redirection; Network request redirection; Performance comparison; Processing overhead; Scalable Web servers; Server capacity; Simulation model; Spatial locality; Temporal locality; Trace driven simulation; Workstations network